Archophileurus spinosus Dechambre, 2006 (Coleoptera: Scarabaeidae: Dynastinae), a new exotic scarab possibly acclimatized in Italy, with a compilation of exotic Scarabaeidae found in Europe - Ruzzier, Enrico; Tomasi, Filippo; Poso, Mattia; Martinez-Sañudo, Isabel (Zootaxa, 2020)
Archophileurus spinosus Dechambre, 2006, a South American Scarabaeidae (Coleoptera: Scarabaeidae: Dynastinae: Phileurini) is recorded for the first time in Europe (Apulia, Italy). This species, which may have colonized the Italian peninsula in recent past and that could still be in the acclimatization phase, represents the first record of tribe Phileurini in Europe and the second case worldwide of interception of this genus outside its area of origin. After a brief presentation of the site and collecting conditions of the specimens, we discuss the possible threats for local biodiversity and agriculture that the establishment of A. spinosus could cause.